Jendela Ontologi Gereja Kristus Tuhan: Merayakan Keunikan Di Tengah Keberagaman Denominasi - Rony Samuel Lere Dawa (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2025)
Dialectical encounters among denominational diversity with all its uniqueness are completely unavoidable. The Church of Christ the Lord (GKT) is one of the denominations that has its own uniqueness to be thanked and celebrated in the midst of denominational diversity with all its uniqueness. This research argument is compiled using a qualitative research method based on a literature review approach. This article intends to look at the uniqueness of GKT (The Church of Christ the Lord) in the midst of the diversity of existing denominations based on a Heideggerian perspective.